Electrochemical reduction of CO2 for synthesis of green fuel. Issue 4 (20th January 2017) - Malik, Karan; Singh, Surya; Basu, Suddhasatwa; Verma, Anil
Abstract : The depletion of increasing CO2 of the atmosphere and the generation of alternate fuel sources are among the biggest challenges being faced by the scientific community across the globe. This scenario has propelled work in the direction of utilization of CO2 by various methods. Electrochemical reduction of CO2 is one of the leading research areas that may be useful not only for the utilization of CO2 but also for the generation of green fuels and storage of renewable energy (solar or wind). However, the process is kinetically impeded and less selective toward a specific product and, therefore, requires efficient electrocatalysts. Much work has already been done in this field, and significant success has also been achieved. Hence, in this review paper, the potential of electrochemical reduction of CO2 for fuel generation is discussed, with special focus on electrocatalysts. The suitability of different electrocatalysts is addressed along with the possible scope for enhancing the efficiency of the process. WIREs Energy Environ 2017, 6:e244. doi: 10.1002/wene.244 This article is categorized under: Fuel Cells and Hydrogen > Climate and Environment Abstract : Schematic of electrochemical reduction of CO2 to various products.